Public Service Interpreter Training: Evaluating the Experiential Learning Approach of the Lives in Translation Internship - Rodriguez, Stephanie A. (International Journal of Language, Translation and Intercultural Communication, 2025)
Lives in Translation (LiT) is a community-based interpreting and translation program at Rutgers University-Newark, educating and training undergraduate students through a combination of structured coursework and experiential internships. LiT’s pedagogical model combines theoretically informed coursework with experiential learning through structured, community-based internship placements. The present study provides the first empirical evaluation of the LiT program, reporting findings from a survey completed by 18 undergraduate students who participated in semester-long internships involving Spanish interpreting assignments with community partners, specifically focused on public service interpreting. The survey assessed students’ overall satisfaction with the academic program and internship, and their development of professional and performance skills through self-assessments. Results of the quantitative analysis show high student satisfaction with the overall academic program and, more specifically, internship experiences. Students reported significant perceived growth in competencies essential to effective public service interpreting, particularly in consecutive interpreting and management of professional boundaries. These findings underscore the value of integrating strategically designed coursework with experiential learning in public service interpreting, offering an adaptable model for institutions aiming to effectively prepare qualified public service interpreters and address growing multilingual demands in their communities.